Oxidation of p-Toluic Acid Hydrazide by Thallium(III) in Acidic Medium: A Kinetic and Mechanistic Study - Varale, Amit; Hilage, Nandini (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of p-toluic acid hydrazide by thallium(III) in a mixture of perchloric acid and hydrochloric acid medium at a constant ionic strength is carried out iodometrically. The reaction proceeds through formation of complex with reactant, which decomposes in subsequent steps to give products. The increase in [H+] and [Cl–] decreases the rate of the reaction. Effect of acrylonitrile shows that there is no formation of free radicals. The effect of temperature was studied at four different temperatures ranging from 15 to 30 ºC. The thermodynamic parameters were also determined and a mechanism is predicted.